ประสิทธิผลการประชาสัมพันธ์ทางการตลาดรถยนต์นั่งส่วนบุคคลขนาดเล็ก - สิปปารี มงคลศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objectives of this research are (1) to study the strategies of marketing public relations and the strategies of brand image for small passenger car (2) to study consumer’s perceptions toward small passenger car image and (3) to study consumer’s buying decision of small passenger car This research can be divided into 2 parts. Part 1 is a qualitative research. The data in use is from interviewed persons who responsible for each brand of small passenger car and supported by relevant documents. Part 2 is a survey research collecting from questionnaire by 400 male and female who live in Bangkok area. Therefore, statistics used in this research are frequency, percentage, mean scores, standard deviation and T-Test. SPSS program is deployed for data processing.The results of this study are:Part 1 The results are the 3 strategies for projecting small passenger car image commonly used (1) Media Mix Strategy (2) Brand Image Strategy (3) Brand Experience Strategy by creating the marketing activities for consumers in order to generate consumer’s perceptions and buying decision. Part 2 The results of hypotheses testing is able to conclude that(1) The consumer’s perceptions for small passenger car is related to consumer’s buying decision at significant level of 0.05 (2) The consumer’s perceptions is related to small passenger car image at significant level of 0.05 (3) The small passenger car image is related to consumer’s buying decision at significant level of 0.05